مساهمة أوليــة في دراسة بيولوجيــا حشــرة جـادوب الصنــوبر Taumetopoeapityocampa Schiff (Taumetopoaeidae: Lepidoptera) في المنطقة الساحلية - إحسان, سليمان (Latakia University Journal -Biological Sciences Series, 2019)
يعتبر جادوب الصنوبر من الحشرات الشائعة في شمال وغرب سوريا ويهاجم الصنوبر البروتي بالدرجة الأولى، تمت دراسة بعض الجوانب البيولوجية والمورفولوجية المتعلقة به. جمع 57 كيس بيض من ثلاثة مواقع (الصوراني ـ القدموس ـ بلوران). تضع الأنثى كيس بيض واحداً خلال حياتها، متوسط عدد البيض في كيس البيض الواحد 214.35 ± 4.29 بيضة تقريباً، كانت نسبة فقس البيض 83.98 % ونسبة البيض غير الفاقس.12.94 % ونسبة التطفل 3.08%. تمر الحشرة بخمسة أعمار يرقية في فترة زمنية مدتها151.5±0.90 يوماً بالمتوسط، مدة العمر اليرقي من العمر الأول إلى العمر الخامس 13.5±0.5 ، 15±1.06 ، 34.75±2.33 ، 39.5±2.08، 48.75±1.08 يوماً بالمتوسط على التوالي. تم تحديد قطر كبسولة الرأس للأعمار اليرقية المختلفة فبلغ 0.70± 0.006، 1.13± 0.006، 1.54 ± 0.015 ، 2.93 ± 0.084، 4.86± 0.124 مم بالمتوسط على التوالي. أما طول الجسم فكان3.44 ± 0.130، 6.08± 0.207، 12.5± 0.130، 20.42 ± 0.909، 33.60± 1.12مم بالمتوسط على التوالي. Some biological and morphological aspects of the Taumetopoeapityocampa spread in north and west of Syria were studied. The meeting between the male and female lasts from 60 minutes. The female lays eggs in ootheca one time in its whole life. The female laid is 214.35± 4.29 eggs. The average of hatched eggs was 83.98%, and of unhatched eggs was12.94. The average of paratism was 3.08 %. The study was carried out in room temperature. Larval instars took 151.5±0.90 days to reach pupa. The five larval ages from the first one to the fifth were 13.5±0.75, 15±1.06, 34.75±2.33, 39.5±2.08 and 48.75±1.08 days respectively on average mean. Some morphological parameters were determined for the different larval instars, including body length and cephalic capsule diameter. The cephalic capsule diameter for five larval in stars were 0.70 ± 0.006, 1.13 ± 0.006, 1.54 ± 0.015, 2.93 ± 0.084, and 4.56 ± 0.124 mm.in average mean. The body length of five larval instars were 3.44 ± 0.130, 6.08 ± 0.207, 12.46 ± 0.130, 20.42 ± 0.909 and 33.60 ± 1.12 mm in average mean.